The Thoracic Shape of Hominoids. (9th April 2014) - Chan, Lap Ki
Abstract : In hominoids, the broad thorax has been assumed to contribute to their dorsal scapular position. However, the dorsoventral diameter of their cranial thorax was found in one study to be longer in hominoids. There are insufficient data on thoracic shape to explain the relationship between broad thorax and dorsal scapular position. The current study presents data on multilevel cross-sectional shape and volume distribution in a range of primates. Biplanar radiographs of intact fluid-preserved cadavers were taken to measure the cross-sectional shape of ten equally spaced levels through the sternum (called decisternal levels) and the relative volume of the nine intervening thoracic segments. It was found that the cranial thorax of hominoids is larger and broader (except in the first two decisternal levels) than that of other primates. The cranial thorax of hominoids has a longer dorsoventral diameter because the increase in dorsoventral diameter caused by the increase in the volume of the cranial thorax overcompensates for the decrease caused by the broadening of the cranial thorax. The larger and broader cranial thorax in hominoids can be explained as a locomotor adaptation for scapular gliding and as a respiratory adaptation for reducing the effects of orthograde posture on ventilation-perfusion inequality.